Gambaran histologik otot jantung pada hewan coba postmortem - Ubruangge, Tonci; Wangko, Sunny; Kalangi, Sonny J.R. (Universitas Sam Ratulangi, 2016)
Abstract: Commonly, unnatural death is complicated and causes difficulties for to the investigating officers to reveal the modus operandi and the time of death. Estimation of postmortem interval is very important in the investigation, albeit, it is frequently put the investigators to a debate. This study aimed to obtain the histological changes of heart muscle at several time intervals postmortem. This was a descriptive observational study. A domestic pig weighed Â±20kg was used as model. The pig was killled by conducting a blunt trauma at its occipital area. Heart muscle samples were taken at several time intervals as follows: 15 minutes, 30 minutes, 45 minutes, 60 minutes, 75 minutes, 90 minutes, 105 minutes, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 12 hours, and 24 hours postmortem. The histological changes were observed with an Olympus CX21 microscope and Optilab. The percentages of those changes were evaluated at 5 high-power fields (400x) for each sample. The results showed that less than 30% of myocytes had flattened and denser nuclei at 105 minutes postmortem and were associated with hydrophic degeneration at 2 hours postmortem. Those changes became widely spreaded and at 24 hours postmortem they could be identified in 60-80% of myocytes. Albeit, the striated pattern could still be identified until 24 hours postmortem. Conclusion: The histological changes of heart muscle postmortem namely morpholocical changes of the nuclei and hydrophic degeneration could be identified at 2 hours postmortem. At 24 hours postmortem those changes were distributed widely among the myocytes, however, the striated pattern could still be identified. Moreover, there were still focal areas with normal appearance. Keywords: histological changes, cardiac muscle, postmortemÂ Abstrak: Kematian tidak wajar yang dialami seseorang dengan berbagai motif kejahatan dapat menyulitkan para penyidik dalam menggungkapkan modus operandi dan waktu kematian. Penentuan lama kematian k orban sangat dibutuhkan dan sering menjadi perdebatan di peradilan. Penelitian ini bertujuan untuk mendapatkan perubahan histologik jaringan otot jantung hewan coba pada beberapa interval waktu postmortem. Jenis penelitian ialah deskriptif-observasional menggunakan hewan coba satu ekor babi lokal dengan berat badan Â±20kg. Hewan coba dimatikan dengan pukulan benda tumpul pada area osipital. Sampel otot jantung diambil pada beberapa interval waktu: 15 menit, 30 menit, 45 menit, 60 menit, 75 menit, 90 menit, 105 menit, 2 jam, 3 jam, 4 jam, 5 jam, 6 jam, 12 jam, dan 24 jam postmortem. Perubahan histologik diamati dengan mikroskop Olympus CX21 dan Optilab. Persentase perubahan tersebut dievaluasi pada 5 lapang pandang pembesaran 400x. Hasil penelitian mendapatkan <30% miosit dengan inti yang memipih dan memadat pada 105 menit postmortem serta degenerasi hidropik 2 jam postmortem. Perubahan-perubahan tersebut makin meluas dan pada 24 jam postmortem telah tampak pada 60-80% miosit jantung tetapi corak seran lintang tetap dapat diidentifikasi. Simpulan: Perubahan histologik berupa perubahan morfologik inti disertai degenerasi hidropik mulai tampak pada 2 jam postmortem dan pada 24 jam postmortem perubahan tersebut telah terdistribusi luas. Walaupun demikian, pada 24 jam postmortem corak seran lintang masih dapat diidentifikasi. Juga terdapat area-area fokal dengan jaringan otot jantung yang masih tampak normal.Kata kunci: perubahan histologik, otot jantung, postmortem